Polyolefin microporous membrane
Patent Information
- Application Number
- JP2020545385
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-22
- Filing Date
- 2020-08-19
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-08-19
AI Technical Summary
【0010】 本発明によれば、高い透過性と優れたシャットダウン特性を有するポリオレフィン微多孔膜を提供することができる。
Smart Images

Figure 0007639341000001 
Figure 0007639341000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a microporous polyolefin membrane having excellent shutdown properties when used as a separator for a secondary battery. [Background technology]
[0002] Microporous membranes are used in various fields, such as filters such as filtration membranes and dialysis membranes, separators for secondary batteries, separators for electrolytic capacitors, etc. Among these, polyolefin microporous membranes made of polyolefin as a resin material are widely used in recent years as separators for secondary batteries because of their excellent chemical resistance, insulating properties, mechanical strength, and shutdown properties.
[0003] Because of their high energy density, secondary batteries, such as lithium-ion secondary batteries, are widely used in personal computers, mobile phones, etc. Secondary batteries are also expected to be used as power sources for driving motors in electric and hybrid vehicles, and as stationary storage batteries.
[0004] In recent years, as the energy density of lithium-ion secondary batteries increases, the thermal stability of the electrodes used tends to decrease (the onset temperature of thermal runaway decreases). Therefore, the polyolefin microporous membranes used in secondary battery separators are required to shut down the battery at a lower temperature when the battery abnormally heats up due to short circuit or overcharging, and to prevent thermal runaway by preventing ion migration between the positive and negative electrodes.
[0005] Patent Document 1 describes a microporous membrane that contains a polyolefin copolymer having a melting point of 122 to 126° C., has a shutdown temperature of 130.5° C. or lower, and has a relatively fast shutdown speed due to the use of a low-molecular-weight polyethylene component. Patent Document 2 discloses a polyethylene microporous membrane having a pore blocking temperature Tf of 134°C or lower and a relationship between the film melting temperature Tm and Tf such that Tm-Tf>0, and claims that when used as a battery separator, the membrane can prevent short circuits during overcharge. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent No. 5536872 [Patent Document 2] Japanese Patent Publication No. 2000-204188 Summary of the Invention [Problem to be solved by the invention]
[0007] In Patent Documents 1 and 2, the microporous membrane achieves a low shutdown temperature by containing a polyethylene component with a low molecular weight and a low melting point, but the inclusion of a polyethylene component with a low molecular weight and a low melting point tends to result in a non-uniform pore structure. A microporous membrane having such a pore structure does not quickly complete shutdown even when exposed to an atmosphere above the shutdown temperature, and when used as a separator for a battery designed for high energy density, such as those being developed in recent years, there have been cases where a problem in ensuring safety has arisen. Such a problem is particularly noticeable in separators with high porosity and excellent permeability.
[0008] The object of the present invention is to solve the above problems by providing a polyolefin microporous membrane that, when used as a battery separator, has excellent permeability and can quickly complete shutdown when exposed to high temperatures inside the battery, thereby providing high safety. [Means for solving the problem]
[0009] In order to solve the above problems and achieve the object, the present invention has the following configuration. [1] The gloss value at an incidence angle of 60° in both the MD and TD directions is 45% or more, and the air permeability converted to a thickness of 10 μm is 300 sec / 100 cm 3 1. A microporous polyolefin membrane comprising: [2] The polyolefin microporous film according to [1], wherein the average value of the gloss value in the MD direction and the gloss value in the TD direction at an incident angle of 60° is 50% or more. [3] The polyolefin microporous membrane according to [1] or [2], which has a shutdown temperature of 135°C or lower. [4] The microporous polyolefin film according to any one of [1] to [3], which has a porosity of 35% or more. [5] The microporous polyolefin film according to any one of [1] to [4], which has an average pore size of 35 nm or less. [6] The microporous polyolefin film according to any one of [1] to [5], which has a pin puncture strength of 1.5 N or more per 10 μm. [7] The microporous polyolefin membrane according to any one of [1] to [6], having a porous layer comprising inorganic particles and a resin binder on at least one surface thereof. Effect of the Invention
[0010] According to the present invention, it is possible to provide a microporous polyolefin membrane having high permeability and excellent shutdown properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention will be described. However, the present invention is not limited to the embodiment described below.
[0012] The polyolefin microporous membrane according to the embodiment of the present invention has a gloss value of 45% or more at an incidence angle of 60° in both the MD and TD directions, and an air permeability of 300 sec / 100 cm per 10 μm thickness. 3 The following is the result.
[0013] The gloss value is a value measured in accordance with JIS Z 8741:1997, and is an index showing the amount of reflected light (glossiness) when a sample is irradiated with light. The gloss value can be measured by the method described below. The gloss value of the microporous membrane according to an embodiment of the present invention at an incident angle of 60° in both the MD and TD directions is 45% or more, preferably 48% or more, more preferably 50% or more, even more preferably 55% or more, and particularly preferably 60% or more.
[0014] When the gloss value of the polyolefin microporous membrane is within the above range, the pores are quickly blocked when the film is exposed to high temperatures, and the battery safety can be improved when the film is used as a separator for a secondary battery. In a polyolefin microporous membrane with a gloss value within the above range, the pores are densely and uniformly formed in the membrane surface structure, and the membrane has a structure with few voids, so that the shutdown behavior proceeds uniformly within the film surface and shutdown is reached with little structural change, and therefore shutdown is presumably completed quickly.
[0015] The gloss value can be adjusted to the above range by adjusting the composition of the polyolefin raw material constituting the microporous membrane to the range described below and by adjusting the membrane-forming conditions to the range described below.
[0016] The upper limit of the gloss value in the MD direction and the TD direction of the polyolefin microporous membrane according to the embodiment of the present invention is not particularly limited, but is, for example, 120% or less, preferably 100% or less. By setting the upper limit of the gloss value in the MD direction and the TD direction in the above range, it is easy to achieve compatibility with permeability. In order to set the gloss value in the MD direction and the TD direction in the above range, it is preferable that the raw material composition of the film is set in the range described later, and the stretching conditions and heat setting conditions during film production are set in the range described later.
[0017] The polyolefin microporous membrane according to the embodiment of the present invention has an air permeability (Gurley value) of 300 sec / 100 cm per 10 μm thickness. 3 The preferred speed is 250 seconds / 100 cm. 3 More preferably, it is 200 seconds / 100 cm or less.3 Less than 150 seconds / 100 cm, more preferably 3 When the air permeability is within the above range, the separator has excellent ion permeability when used as a battery separator, and a secondary battery incorporating the separator has a reduced impedance and improved battery output and rate characteristics. The lower limit of the air permeability calculated based on a thickness of 10 μm is, for example, 10 sec / 100 cm 3 More than 50 seconds / 100 cm is preferable. 3 That is all. When the lower limit of the air permeability is within the above range, it is easy to achieve compatibility with the film strength. In order to set the air permeability in terms of a thickness of 10 μm within the above range, it is preferable that the raw material composition of the film is within the range described below, and that the stretching conditions and heat setting conditions during film production are within the ranges described below.
[0018] In the polyolefin microporous membrane according to an embodiment of the present invention, the average value of the gloss value in the MD direction and the gloss value in the TD direction (average gloss value) at an incident angle of 60° is preferably 50% or more, more preferably 55% or more, even more preferably 60% or more, and particularly preferably 63% or more.
[0019] When the average gloss value of the polyolefin microporous membrane is within the above range, the pores are quickly blocked when the film is exposed to high temperatures, and when the film is used as a separator for a secondary battery, the battery safety can be improved. In the polyolefin microporous membrane having the average gloss value within the above range, the pores are densely and uniformly formed in the membrane surface structure, and the membrane has a structure with few voids, so that the shutdown behavior in the film plane proceeds uniformly and shutdown is reached with little structural change, and therefore the shutdown is completed quickly.
[0020] The upper limit of the average gloss value of the polyolefin microporous membrane according to the embodiment of the present invention is not particularly limited, but is, for example, 120% or less, preferably 100% or less. By setting the upper limit of the average gloss value in the above range, it is easy to achieve compatibility with permeability. In order to set the average gloss value in the above range, it is preferable that the raw material composition of the film is within the range described below, and that the stretching conditions and heat setting conditions during film production are within the range described below.
[0021] The shutdown temperature of the polyolefin microporous membrane according to the embodiment of the present invention is preferably 135°C or lower, more preferably 132°C or lower, even more preferably 130°C or lower, and particularly preferably 129°C or lower. By controlling the shutdown temperature to 135°C or lower, the battery safety is excellent when the membrane is used as a battery separator. The lower limit of the shutdown temperature is not particularly limited, but is preferably 100°C or higher, since it is possible to suppress a decrease in ion permeability due to pore blockage during membrane formation. To set the shutdown temperature in the above range, it is preferable that the raw material composition of the film is within the range described below, and that the stretching conditions and heat setting conditions during film formation are within the range described below.
[0022] The shutdown temperature is measured by the method described below, and is the temperature at which, when the polyolefin microporous membrane is heated, the resin portion shrinks and melts, closing the porous structure, making it substantially impossible to discharge or charge the membrane when used as a battery separator.
[0023] The porosity of the polyolefin microporous membrane according to the embodiment of the present invention is preferably 35% or more, more preferably 40% or more, and even more preferably 45% or more. There is no particular upper limit to the porosity, but it is preferably 75% or less in order to prevent a decrease in membrane strength. By having the porosity in the above range, the output characteristics are excellent when used as a separator for a secondary battery.
[0024] The porosity can be adjusted to the above range by adjusting the blending ratio of the polyolefin components, the stretching ratio, the heat setting conditions, and the like during the production process.
[0025] The average pore size (mean flow diameter) of the polyolefin microporous membrane according to the embodiment of the present invention is preferably 35 nm or less, more preferably 32 nm or less, even more preferably 30 nm or less, and particularly preferably 27 nm or less. A separator having an average pore size in the above range has an excellent balance between strength and permeability, and when the polyolefin microporous membrane is used as a battery separator, shutdown is quickly completed in the event of abnormal heat generation, resulting in excellent battery safety. There is no particular lower limit for the average pore size, but a value of 5 nm or more is preferable because good permeability can be easily obtained.
[0026] The average pore size is a value measured by a method in accordance with ASTM E1294-89 (half-dry method), and can be measured by the method described below.
[0027] The pin puncture strength per 10 μm of the polyolefin microporous membrane according to the embodiment of the present invention is preferably 1.5 N or more, more preferably 1.8 N or more, even more preferably 2.2 N or more, and particularly preferably 2.5 N or more. There is no particular upper limit to the pin puncture strength per 10 μm, but it is preferably, for example, 8.0 N or less, since this makes it easy to control the shutdown temperature within an appropriate range. When the 10 μm converted pin puncture strength is within the above range, the occurrence of electrode short-circuiting is suppressed in a secondary battery using this as a separator.
[0028] The 10 μm equivalent pin puncture strength can be adjusted to the above range by adjusting the weight average molecular weight (Mw) of the raw material resin and the stretching conditions when producing the polyolefin microporous membrane.
[0029] The thickness of the polyolefin microporous membrane according to the embodiment of the present invention is preferably 20 μm or less, more preferably 15 μm or less, even more preferably 13 μm or less, and particularly preferably 9 μm or less. There is no particular lower limit to the thickness, but it is preferably 1 μm or more because it can suppress the occurrence of short circuits when used as a separator for a secondary battery. When the thickness is within the above range, the battery capacity is improved by using the polyolefin microporous membrane as a separator for a secondary battery.
[0030] Hereinafter, a specific configuration of the polyolefin microporous membrane of the present embodiment will be described, but the present invention is not necessarily limited thereto.
[0031] The polyolefin microporous membrane according to the embodiment of the present invention contains a polyolefin resin as a main component. The main component here refers to the component that constitutes the polyolefin microporous membrane in the largest mass%. The polyolefin resin is preferably contained in an amount of 80 mass% or more, more preferably 90 mass% or more, based on the total mass of the polyolefin microporous membrane.
[0032] Examples of polyolefin resins include polyethylene resins and polypropylene resins, and polyethylene resins are preferred as the main component from the viewpoint of a balance of functions such as shutdown behavior, strength, and permeability.
[0033] As the polyethylene-based resin, various types of polyethylene can be used, including ultra-high molecular weight polyethylene, high density polyethylene, medium density polyethylene, and low density polyethylene.
[0034] The polyethylene resin may be a homopolymer of ethylene or a copolymer of ethylene and another α-olefin, such as propylene, butene-1, hexene-1, pentene-1, 4-methylpentene-1, octene, vinyl acetate, methyl methacrylate, or styrene.
[0035] The polyolefin microporous membrane according to the embodiment of the present invention may be a single-layer membrane, but it can also be a laminate membrane consisting of at least two layers having different properties, where layer A is made of polyolefin resin A mainly composed of a polyolefin resin, and layer B is made of a polyolefin resin (referred to as polyolefin resin B) mainly composed of a polyolefin resin having different properties.
[0036] Examples of the layer structure include layer A only, layer A / layer B, layer A / layer B / layer A, layer B / layer A / layer B, etc., among which, layer A only and layer A / layer B / layer A structures are preferred, and layer A / layer B / layer A structure is particularly preferred. By using the layer structure as described above, it is easy to set the gloss value of the polyolefin microporous membrane according to an embodiment of the present invention within an appropriate range, and good shutdown properties and permeability can be achieved at the same time.
[0037] In the polyolefin microporous membrane according to the embodiment of the present invention, the ratio of the thickness of layer A to the total thickness of all layers is preferably 50% or less, more preferably 40% or less, even more preferably 30% or less, and most preferably 20% or less. By setting the raw materials constituting layer A within the ranges described below, the polyolefin microporous membrane according to the embodiment of the present invention can effectively impart a shutdown function even if the ratio of the thickness of layer A is small.
[0038] When the polyolefin microporous membrane according to the embodiment of the present invention has a plurality of layers A, the total thickness of the layers A is preferably 6.0 μm or less, more preferably 5.0 μm or less, even more preferably 4.0 μm or less, and most preferably 3.0 μm or less. By setting the raw materials constituting the layers A in the ranges described below, the polyolefin microporous membrane according to the embodiment of the present invention can effectively impart a shutdown function even if the thickness of the layers A is thin.
[0039] Polyolefin resin A is made of high-density polyethylene (density: 0.940 g / m) from the viewpoints of melt extrusion properties and stretch processing properties. 3 More than 0.970g / m 3It is preferable that the polyethylene resin (polyethylene (A)) used in polyolefin resin A is not only an ethylene homopolymer, but also a copolymer containing other α-olefins in order to lower the melting point and crystallinity of polyolefin resin A. Examples of α-olefins include propylene, butene-1, hexene-1, pentene-1, 4-methylpentene-1, octene, vinyl acetate, methyl methacrylate, and styrene. As the copolymer containing an α-olefin, a copolymer containing hexene-1 (ethylene-1-hexene copolymer) is preferable, and it is more preferable that polyethylene (A) is mainly composed of an ethylene-1-hexene copolymer. In addition, the α-olefin is preferably C 13 This can be confirmed by measuring with -NMR.
[0040] In addition, it is more preferable that polyolefin resin A contains a branched polyethylene, since this allows for the formation of a uniform fine pore structure and suppresses crystal orientation during stretching, resulting in a polyolefin microporous film with excellent shutdown properties.
[0041] The branched polyethylene is contained in the polyolefin microporous membrane in an amount of preferably 10% by mass or more, more preferably 30% by mass or more, further preferably 50% by mass or more, and particularly preferably 70% by mass or more, based on the total mass of layer A. This makes it easy to adjust the gloss value of the polyolefin microporous membrane according to the embodiment of the present invention to an appropriate range, and provides a polyolefin microporous membrane with excellent shutdown properties.
[0042] The lower limit of the weight average molecular weight of the branched polyethylene is preferably 1×10 4 More preferably, it is 1×10 5 More preferably, 1.5×10 5 The upper limit of the weight average molecular weight of the branched polyethylene is 1×10 6 Less than or equal to 8.0×10 5 Less than 6.0×10, more preferably 5By setting the weight average molecular weight of the branched polyethylene within the above range, it is possible to achieve both a low shutdown temperature and a high film strength during shutdown.
[0043] The melting point of the branched polyethylene is preferably 136°C or lower, more preferably 135°C or lower, and even more preferably 133°C or lower. Also, it is preferably 115°C or higher, more preferably 120°C or higher, and even more preferably 125°C or higher. By setting the melting point within the above range, both a low shutdown temperature and the permeability of the polyolefin microporous membrane can be achieved. The melting point of the branched polyethylene can be measured by the method described below.
[0044] Furthermore, by adding low-density polyethylene, linear low-density polyethylene, ethylene-α-olefin copolymer produced with a single-site catalyst, low-molecular-weight polyethylene with a weight-average molecular weight of 1,000 to 100,000, etc. as polyolefin resin A, a shutdown function at low temperatures is imparted, and the properties as a battery separator can be improved. However, if the proportion of the above-mentioned low-molecular-weight polyethylene added as polyolefin resin A is high, the porosity of the microporous film decreases during the film-forming process, and it is necessary to use a polyolefin resin having a density of 0.94 g / cm as the ethylene-α-olefin copolymer. 3 It is preferable to add a high density polyethylene exceeding 100% by weight, and it is even more preferable to add a branched polyethylene containing long chain branches, since this can maintain the porosity while improving the shutdown characteristics as described above.
[0045] From the above viewpoints, the molecular weight distribution of the polymer constituting the polyolefin microporous membrane according to the embodiment of the present invention is preferably such that the amount of components with a molecular weight of less than 40,000 is less than 20%. More preferably, the amount of components with a molecular weight of less than 20,000 is less than 20%, and even more preferably, the amount of components with a molecular weight of less than 10,000 is less than 20%. By using the above-mentioned raw materials, it is possible to lower the shutdown temperature without significantly reducing the molecular weight, and as a result, it is possible to achieve compatibility with other physical properties such as strength and porosity.
[0046] From the viewpoints of melt extrusion properties, stretch processing properties, and the permeability and strength of the obtained polyolefin microporous membrane, polyolefin resin B preferably contains high-density polyethylene in an amount of preferably 10 mass% or more, more preferably 30 mass% or more, even more preferably 50 mass% or more, and particularly preferably 60 mass% or more, based on the total mass of layer B in the polyolefin microporous membrane.
[0047] The lower limit of the weight average molecular weight of the high density polyethylene is preferably 1×10 5 More preferably, it is 2×10 5 More preferably, 3×10 5 The upper limit of the weight average molecular weight of high density polyethylene is 1 × 10 6 Less than or equal to 8.0×10 5 Less than 6.0×10, more preferably 5 By setting the weight average molecular weight of the high density polyethylene contained in polyolefin resin B within the above range, good film formation stability can be obtained when laminated with layer A, and good permeability and film strength can also be obtained.
[0048] The melting point of the high density polyethylene is preferably 135° C. to 140° C. By setting the melting point of the high density polyethylene within the above range, good permeability and membrane strength can be obtained. The melting point of the high density polyethylene can be measured by the method described below.
[0049] The use of a polypropylene-based resin as a part of the polyolefin-based resin contained in the polyolefin resin A and the polyolefin resin B is preferable from the viewpoint of improving the meltdown temperature when the polyolefin microporous membrane according to the embodiment of the present invention is used as a separator for a secondary battery. The meltdown temperature is the temperature at which the separator melts and breaks when the battery abnormally heats up, and the higher the temperature, the more preferable it is from the viewpoint of battery safety. In addition to homopolypropylene, block copolymers and random copolymers can also be used as the type of polypropylene-based resin. The block copolymers and random copolymers can contain a copolymer component with an α-olefin other than propylene, and ethylene is preferred as the α-olefin.
[0050] The amount of polypropylene resin added to the polyolefin microporous membrane is preferably 30% by mass or less, more preferably 20% by mass or less, based on the total mass of the polyolefin microporous membrane, which makes it easier to control the shutdown temperature, strength, and permeability within appropriate ranges.
[0051] Polyolefin resin A and polyolefin resin B may contain resin components other than polyethylene-based resin and polypropylene-based resin as necessary. Furthermore, various additives such as antioxidants, heat stabilizers, antistatic agents, ultraviolet absorbers, antiblocking agents, fillers, crystal nucleating agents, and crystallization retarders may be contained within the range that does not impair the effects of the present invention.
[0052] The microporous polyolefin membrane according to an embodiment of the present invention may have one or more coating layers on at least one surface.
[0053] Examples of the coating layer include other porous layers other than polyolefin resins. The other porous layers are not particularly limited, but are preferably, for example, porous layers such as inorganic particle layers containing resin binders and inorganic particles. The resin binder components constituting the inorganic particle layer are not particularly limited, and known components can be used, for example, acrylic resins, polyvinylidene fluoride resins, polyamideimide resins, polyamide resins, aromatic polyamide resins, polyimide resins, etc. can be used. The inorganic particles constituting the inorganic particle layer are not particularly limited, and known materials can be used, for example, alumina, boehmite, barium sulfate, magnesium oxide, magnesium hydroxide, magnesium carbonate, silicon, etc. can be used.
[0054] Next, the method for producing the polyolefin microporous membrane in the embodiment of the present invention will be described. The method for producing the polyolefin microporous membrane can be, for example, a dry membrane production method or a wet membrane production method. As the method for producing the polyolefin microporous membrane in the present embodiment, the wet membrane production method is preferred from the viewpoint of controlling the structure and physical properties of the membrane.
[0055] A wet method for producing a polyolefin microporous membrane will be described below. Note that the following description is merely an example of the production method, and the present invention is not limited to this method.
[0056] A method for producing a polyolefin microporous membrane in an embodiment of the present invention preferably includes the following steps (1) to (5) and may further include the following step (6), and may also include at least one of the following steps (7) and (8).
[0057] (1) A step of melt-kneading the polyolefin resin and a membrane-forming solvent to prepare a polyolefin resin composition. (2) A step of extruding the polyolefin resin composition and cooling it to form a gel-like sheet. (3) A first stretching step of preheating and stretching the gel-like sheet (4) A step of removing the membrane-forming solvent from the stretched gel-like sheet. (5) A step of drying the sheet after removing the membrane-forming solvent. (6) A second stretching step of preheating and stretching the dried sheet (7) A step of heat treating the dried sheet (8) A step of subjecting the dried sheet to a crosslinking treatment and / or hydrophilization treatment.
[0058] Each step will be described below. In the following description, a numerical range indicated with "to" means a range including the numerical values before and after "to" as the lower and upper limits.
[0059] (1) Preparation of polyolefin resin composition A polyolefin resin composition is prepared by dissolving a polyolefin resin in a plasticizer (membrane-forming solvent) by heating. The plasticizer is not particularly limited as long as it is a solvent that can sufficiently dissolve the polyolefin resin, but in order to enable relatively high-magnification stretching, it is preferable that the solvent is liquid at room temperature. Examples of the solvent include aliphatic, cycloaliphatic, or aromatic hydrocarbons such as nonane, decane, decalin, paraxylene, undecane, dodecane, and liquid paraffin, and mineral oil fractions having boiling points corresponding thereto, as well as phthalic acid esters that are liquid at room temperature, such as dibutyl phthalate and dioctyl phthalate. In order to obtain a gel-like sheet with a stable content of the liquid solvent, it is preferable to use a nonvolatile liquid solvent such as liquid paraffin.
[0060] The blending ratio of the polyolefin resin and the plasticizer may be appropriately selected within a range that does not impair moldability, but the content of the polyolefin resin is preferably 10 to 50 mass% relative to the total mass of the polyolefin resin composition. When the polyolefin resin is 10 mass% or more, swelling and necking at the outlet of the die are not large when the composition is molded into a sheet, so that the moldability and film formability of the sheet are good. On the other hand, when the polyolefin resin is 50 mass% or less, shrinkage in the thickness direction is suppressed, and moldability is good.
[0061] The method for uniformly melt-kneading the polyolefin resin and the plasticizer is not particularly limited, but is preferably carried out in a twin-screw extruder.
[0062] The resin temperature during kneading is preferably 140°C or higher for a polyolefin resin composition consisting of polyolefin resin A, more preferably 150°C or higher, and even more preferably 160°C or higher, with the upper limit being preferably 250°C or lower, more preferably 200°C or lower, and even more preferably 180°C or lower.
[0063] Furthermore, for the polyolefin resin composition consisting of polyolefin resin B, the temperature is preferably 170°C or higher, more preferably 180°C or higher, and even more preferably 190°C or higher, and the upper limit is preferably 250°C or lower, more preferably 230°C or lower, and even more preferably 220°C or lower.
[0064] By keeping the temperature of the polyolefin resin composition during kneading within the above range, it is possible to prevent a decrease in strength due to deterioration of the resin, and it is possible to melt-knead the polyolefin resin and the plasticizer uniformly.
[0065] In addition, during kneading with a twin-screw extruder, the Q / Ns calculated from the ratio of the extrusion mass Q (kg / hr) to the screw rotation speed Ns (rpm) is preferably 0.05 or more, more preferably 0.1 or more, and even more preferably 0.15 or more. This can prevent a decrease in strength due to resin deterioration during kneading. In addition, the upper limit is preferably 3.0 or less, more preferably 2.0 or less, and particularly preferably 1.0 or less, which allows sufficient shear to be applied to the polyolefin resin composition and allows a uniform dispersion state to be obtained.
[0066] (2) Gel-like sheet formation process The melt of the polyolefin resin composition is fed from the extruder to a die and extruded into a sheet.
[0067] The extrusion method may be either a flat die method or an inflation method. In addition, a plurality of polyolefin resin compositions having the same or different compositions may be fed from a plurality of extruders to one multi-manifold type composite T-die, laminated in layers, and extruded into a sheet having a laminated structure. The extrusion temperature is preferably 140 to 250°C, and the extrusion speed is preferably 0.2 to 15 m / min. The resin composition melt-extruded into a sheet is cooled and solidified to become a gel-like sheet. In the cooling step, it is preferable to cool to 10 to 50°C. This is because it is preferable to set the final cooling temperature below the crystallization end temperature, and by making the high-order structure finer, it becomes easier to perform uniform stretching in the subsequent stretching. In addition, the cooling rate at this time is preferably 50°C / min or more, more preferably 100°C / min or more, and even more preferably 150°C / min or more. In general, when the cooling rate is slow, relatively large crystals are formed, so that the high-order structure of the gel-like sheet becomes coarse, and the gel structure that forms it also becomes large. On the other hand, if the cooling rate is fast, relatively small crystals are formed, so the higher-order structure of the gel-like sheet becomes dense, leading to uniform stretching and improved strength and elongation of the film. The cooling method at this time includes direct contact with cold air, cooling water, or other cooling medium, contact with a roll cooled with a refrigerant, and the use of a casting drum.
[0068] (3) First stretching step Next, the obtained gel-like sheet is stretched at least uniaxially, but it is preferable to preheat the gel-like sheet before stretching. The preheating temperature is preferably 90 to 130° C., more preferably 105 to 120° C., and even more preferably 110 to 117° C. By preheating at the above conditions, a polyolefin microporous membrane that is uniformly stretched in the stretching step and has a uniform and fine pore structure can be obtained.
[0069] The preheating time is preferably 5 seconds or more, more preferably 15 seconds or more, even more preferably 60 seconds or more, and particularly preferably 180 seconds or more. By setting the preheating time within the above range, the temperature distribution in the gel sheet becomes uniform, and the crystal structure is stabilized, so that the film is uniformly stretched in the subsequent stretching step, and a polyolefin microporous film having a uniform fine pore structure can be obtained. There is no particular upper limit for the preheating time, but from the viewpoint of productivity, it is preferably 1000 seconds or less.
[0070] The preheated gel-like sheet is preferably stretched at a predetermined magnification by a tenter method, a roll method, an inflation method, or a combination of these. The stretching may be uniaxial or biaxial, with biaxial stretching being preferred. In the case of biaxial stretching, any of simultaneous biaxial stretching, sequential stretching, and multi-stage stretching (e.g., a combination of simultaneous biaxial stretching and sequential stretching) may be used.
[0071] The stretching ratio (area stretching ratio) in this step is preferably 16 times or more, more preferably 25 times or more. In addition, it is preferably 5 times or more in both the machine longitudinal direction and the machine width direction (MD direction and TD direction), and the stretching ratios in the MD direction and the TD direction may be the same or different. By setting the area stretching ratio within the above range, mechanical strength and permeability can be improved. In addition, the area stretching ratio is preferably 100 times or less, more preferably 80 times or less, which can prevent membrane rupture and suppress an increase in the shutdown temperature. The stretching ratio in this step refers to the area stretching ratio of the polyolefin microporous membrane immediately before being subjected to the next step, based on the polyolefin microporous membrane immediately before this step.
[0072] The stretching temperature in this step is preferably within the range of the crystal dispersion temperature (TCD) of the polyolefin resin to TCD+30° C., more preferably within the range of TCD+5° C. to TCD+28° C., and particularly preferably within the range of TCD+10° C. to TCD+26° C. When the stretching temperature is within the above range, film rupture due to stretching of the polyolefin resin is suppressed, and high-magnification stretching is possible.
[0073] The crystal dispersion temperature (TCD) is determined by measuring the temperature characteristics of dynamic viscoelasticity according to ASTM D 4065. When a polyethylene resin is used as the polyolefin resin, the ultra-high molecular weight polyethylene, polyethylene other than the ultra-high molecular weight polyethylene, and polyethylene resin compositions have a crystal dispersion temperature of about 100 to 110°C, so the stretching temperature is preferably 90 to 130°C, more preferably 105 to 120°C, and even more preferably 110 to 117°C.
[0074] The above-mentioned stretching causes cleavage between the polyethylene lamellae, resulting in finer polyethylene resin phases and the formation of numerous fibrils, which form a three-dimensionally irregularly connected network structure.
[0075] (4) Removal of membrane-forming solvent The membrane-forming solvent is removed (washed) using a washing solvent. Since the polyolefin resin phase is phase-separated from the membrane-forming solvent phase, when the membrane-forming solvent is removed, a porous membrane is obtained that is made of fibrils that form a fine three-dimensional network structure and has holes (voids) that are three-dimensionally irregularly connected. The washing solvent and the method of removing the membrane-forming solvent using the same are publicly known, so the explanation is omitted. For example, the methods disclosed in Japanese Patent No. 2132327 and Japanese Patent Publication No. 2002-256099 can be used.
[0076] (5) Drying The polyolefin microporous membrane from which the membrane-forming solvent has been removed is dried by heat drying or air drying. The drying temperature is preferably equal to or lower than the crystal dispersion temperature (TCD) of the polyolefin resin, and more preferably 5° C. or more lower than the TCD. The drying is preferably carried out until the amount of the remaining washing solvent is 5 parts by mass or less, more preferably 3 parts by mass or less, per 100 parts by mass (dry mass) of the total mass of the polyolefin microporous membrane.
[0077] (6) Second stretching step The dried polyolefin microporous membrane may be stretched at least uniaxially (second stretching step). The film may be preheated before the second stretching step. The preheating temperature is preferably 90 to 140°C, more preferably 95 to 135°C, and even more preferably 100 to 130°C. The polyolefin microporous membrane may be stretched while being heated by a tenter method, a roll method, an inflation method, or the like, as described above. The stretching may be uniaxial or biaxial. In the case of biaxial stretching, either simultaneous biaxial stretching or sequential stretching may be used.
[0078] The stretching temperature in this step is not particularly limited, but is usually 90 to 140°C, more preferably 95 to 130°C, and further preferably 100 to 130°C.
[0079] The area stretching ratio in this step is preferably 16.0 times or less, more preferably 4.0 times or less, and even more preferably 2.0 times or less. In the case of biaxial stretching, the stretching ratios in the MD direction and the TD direction may be the same or different. The stretching ratio in this step refers to the stretching ratio of the polyolefin microporous membrane immediately before the step, based on the polyolefin microporous membrane immediately before the step.
[0080] (7) Heat treatment The polyolefin microporous membrane after drying may be subjected to a heat treatment. The heat treatment stabilizes the crystals and makes the lamellae uniform. Heat setting and / or heat relaxation may be used as the heat treatment method. Heat setting is a heat treatment in which the membrane is heated while maintaining its dimensions. Heat relaxation is a heat treatment in which the membrane is thermally shrunk in the MD or TD direction during heating. The heat setting is preferably performed by a tenter method or a roll method. For example, the heat relaxation method may be the method disclosed in Japanese Patent Application Laid-Open No. 2002-256099. The heat treatment temperature is preferably within the range of TCD to the melting point of the polyolefin resin. The melting point can be measured by a differential scanning calorimeter (DSC) based on JIS K7121 (1987).
[0081] (8) Cross-linking treatment, hydrophilization treatment Furthermore, the dried microporous polyolefin membrane may be further subjected to a crosslinking treatment and a hydrophilization treatment.
[0082] For example, the crosslinking treatment is performed by irradiating the polyolefin microporous membrane with ionizing radiation such as α-rays, β-rays, γ-rays, and electron beams. In the case of electron beam irradiation, the electron beam dose is preferably 0.1 to 100 MRAD, and the acceleration voltage is preferably 100 to 300 KV. The crosslinking treatment increases the meltdown temperature of the polyolefin microporous membrane.
[0083] The hydrophilization treatment can be carried out by monomer grafting, surfactant treatment, corona discharge, etc. The monomer grafting is preferably carried out after the crosslinking treatment.
[0084] The polyolefin microporous membrane obtained as described above can be used for various applications such as a filter, a fuel cell separator, and a condenser separator. In particular, when used as a battery separator, it has excellent permeability and can impart high safety, and therefore can be preferably used as a battery separator for secondary batteries that require high energy density, high capacity, and high output, such as for electric vehicles. EXAMPLES
[0085] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples. Moreover, Examples 1, 3, 5, and 7 shall be read as Reference Examples 1, 3, 5, and 7, respectively.
[0086] [Measurement method] [Film thickness] The thickness of the polyolefin microporous membrane was measured at five points within a 50 mm x 50 mm area using a contact thickness gauge, Litematic VL-50 (10.5 mmφ ultrahard spherical probe, measuring load 0.01 N) manufactured by Mitutoyo Corporation, and the average value was recorded as the thickness (μm).
[0087] [Porosity] A sample of 50 mm × 50 mm square was cut from the polyolefin microporous membrane, and its volume (cm) at room temperature (25°C) was measured. 3 ) and mass (g). These values and the film density (g / cm 3 ) The porosity of the polyolefin microporous membrane was calculated from the following formula.
[0088] Porosity (%) = (volume-mass / film density) / volume x 100
[0089] The film density is 0.99 g / cm 3 The calculations were performed assuming a constant value of
[0090] [10μm equivalent puncture strength] The puncture strength was measured in accordance with JIS Z 1707 (2019), except that the test speed was 2 mm / sec. Using a force gauge (IMADA Co., Ltd., DS2-20N), the maximum load (N) was measured when a polyolefin microporous membrane was punctured in an atmosphere of 25°C with a 1.0 mm diameter needle with a spherical tip (radius of curvature R: 0.5 mm), and the puncture strength when the membrane was 10 μm thick was calculated using the following formula.
[0091] Formula: Puncture strength (10 μm equivalent) (N) = Maximum load (N) × 10 (μm) / Polyolefin microporous membrane thickness (μm)
[0092] [Air permeability] Film thickness T 1 (μm) polyolefin microporous membrane, the air permeability (sec / 100cm) was measured in an atmosphere of 25°C using an Oken air permeability meter (Asahi Seiko Co., Ltd., EGO-1T) in accordance with JIS P-8117. 3 The air permeability (converted to 10 μm) (sec / 100 cm) when the membrane thickness was 10 μm was also measured using the following formula: 3 ) was calculated.
[0093] Formula: Air permeability (10μm conversion) (sec / 100cm 3 ) = Air permeability (sec / 100cm 3 )×10(μm) / polyolefin microporous membrane thickness(μm)
[0094] [Gloss value] In accordance with JIS Z-8741 (1997), measurements were taken using a digital variable angle glossmeter UGV-5D manufactured by Suga Test Instruments Co., Ltd. at an incidence angle of 60° and a receiving angle of 60°.
[0095] For both surfaces of the polyolefin microporous membrane, measurements were taken at three points so that the incident and received light of the glossmeter were parallel to the MD direction of the film sample, and the average of the three gloss values measured at each surface was calculated. The value of the surface with the highest average value was used as the MD gloss value of the polyolefin microporous membrane.
[0096] In addition, measurements were taken at three points on each surface of the polyolefin microporous membrane so that the incident and received light of the glossmeter were parallel to the TD direction of the film sample, and the average of the three gloss values measured at each surface was calculated. The value of the surface with the highest average value was regarded as the gloss value in the TD direction of the polyolefin microporous membrane.
[0097] In addition, the average of the MD gloss value and the TD gloss value calculated by the above-mentioned method was calculated as the average gloss value.
[0098] [Shutdown temperature] The polyolefin microporous membrane was heated at a heating rate of 5°C / min while measuring the air permeability resistance with an air permeability meter (EGO-1T, manufactured by Asahi Seiko Co., Ltd.). 5 seconds / 100cm 3 The temperature at which air reached was determined and taken as the shutdown temperature (°C).
[0099] The measurement cell was composed of an aluminum block and had a structure in which a thermocouple was placed directly under the polyolefin microporous membrane. The sample was cut into a 5 cm x 5 cm square and heated while being fixed with an O-ring around the periphery.
[0100] [Average pore diameter] Measurements were performed using a perm porometer (CFP-1500A, manufactured by PMI). GALWICK (surface tension: 15.9 dynes / cm) was used as the impregnation liquid for the polyolefin microporous membrane, and measurements were performed in the order of dry-up and wet-up. The average pore size (average flow diameter) (nm) was calculated from the pressure at the point where the curve showing the half slope of the pressure-flow curve in the dry-up measurement intersects with the curve in the wet-up measurement, and this was taken as the average pore size. The following formula was used to convert the pressure to the pore size of the microporous membrane.
[0101] d=C·γ / P (In the above formula, "d (nm)" is the pore size of the microporous membrane, "γ (dynes / cm)" is the surface tension of the impregnating liquid, "P (KPa)" is the pressure, and "C" is a constant, which is set to 2860.)
[0102] [Weight average molecular weight of polyolefin resin] The weight average molecular weight (Mw) and molecular weight distribution (MwD) of the polyolefin resin were determined by gel permeation chromatography (GPC) under the following conditions. Measurement equipment: Waters Corporation GPC-150C Column: Showa Denko Shodex UT806M Column temperature: 135℃ Solvent (mobile phase): o-dichlorobenzene Solvent flow rate: 1.0 ml / min Sample concentration: 0.1 wt% (dissolution conditions: 135℃ / 1h) Injection volume: 500μl Detector: Waters Corporation differential refractometer (RI detector) Calibration curve: A calibration curve was created using a polyethylene conversion factor (0.46) from a calibration curve obtained using a monodisperse polystyrene standard sample.
[0103] [Differential Scanning Calorimetry (DSC)] The melting point of the raw polyolefin resin was measured by differential scanning calorimetry (DSC). 6.0 mg of the sample was sealed in an aluminum pan and heated from 30°C to 230°C at 10°C / min (first heating) using a Parker Elmer PYRIS Diamond DSC, then held at 230°C for 5 minutes, cooled at a rate of 10°C / min, and heated again from 30°C to 230°C at a heating rate of 10°C / min (second heating). The temperature at the peak top of the melting peak obtained in the second heating was taken as the melting point of the raw resin.
[0104] Example 1 Polyolefin resin A has a weight average molecular weight (Mw) of 2.5×10 5 A mixture of 100% by mass of branched polyethylene having a melting point of 133°C, 39.8% by mass of the polyolefin resin A, and 0.2% by mass of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)-propionate]methane as an antioxidant was fed into a twin-screw extruder, 60% by mass of liquid paraffin was fed from the side feeder of the twin-screw extruder, and the mixture was melt-kneaded under the conditions of a temperature of 160°C, a cylinder rotation speed of 250 rpm, and Q / Ns=0.2 to prepare a polyolefin resin composition A. The polyolefin resin composition A was fed into a T-die, extruded into a sheet, and cooled while being taken up at a take-up speed of 4 m / min with a cooling roll adjusted to a temperature of 30°C to form a gel-like sheet.
[0105] The gel-like sheet obtained was cut into a square of 80 mm square, preheated at 110°C for 300 seconds, and simultaneously biaxially stretched 5 times in the MD direction and 5 times in the TD direction at a stretching temperature of 110°C and a stretching speed of 1000 mm / min. The stretched membrane was washed in a washing tank of methylene chloride to remove liquid paraffin, dried in a drying oven adjusted to 20°C, and heat-set in an electric oven at 120°C for 10 minutes to obtain a polyolefin microporous membrane.
[0106] Example 2 Polyolefin resin A has a weight average molecular weight (Mw) of 2.5×10 5A mixture of 100 mass% branched polyethylene having a melting point of 133°C, 39.8 mass% of the above polyolefin resin A, and 0.2 mass% of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)propionate]methane as an antioxidant was charged into a twin-screw extruder, 60 mass% of liquid paraffin was fed from the side feeder of the twin-screw extruder, and the mixture was melt-kneaded under conditions of a temperature of 160°C, a cylinder rotation speed of 250 rpm, and Q / Ns = 0.2 to prepare polyolefin resin composition A.
[0107] Polyolefin resin B has a weight average molecular weight (Mw) of 6.0×10 5 60% by mass of high-density polyethylene with a melting point of 136°C and a weight-average molecular weight (Mw) of 2.0 × 10 6 40% by mass of ultra-high molecular weight polyethylene having a melting point of 133°C was used, and 24.8% by mass of the polyolefin resin B and 0.2% by mass of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)-propionate]methane, which is an antioxidant, were mixed and fed into a twin-screw extruder, and 75% by mass of liquid paraffin was fed from the side feeder of the twin-screw extruder. The mixture was melt-kneaded under the conditions of a temperature of 200°C, a cylinder rotation speed of 250 rpm, and Q / Ns=0.2 to prepare a polyolefin resin composition B. The polyolefin resin composition A and the polyolefin resin composition B were fed from each twin-screw extruder to a three-layer T-die and extruded into a sheet shape with a layer structure of A layer / B layer / A layer with a layer ratio of 1 / 3 / 1. The mixture was cooled while being taken up at a take-up speed of 8 m / min with a cooling roll adjusted to a temperature of 30°C to form a gel-like sheet.
[0108] The gel-like sheet obtained was cut into a square of 80 mm square, preheated at 115°C for 300 seconds, and simultaneously biaxially stretched 5 times in the MD direction and 5 times in the TD direction at a stretching temperature of 115°C and a stretching speed of 1000 mm / min. The stretched membrane was washed in a washing tank of methylene chloride to remove liquid paraffin, dried in a drying oven adjusted to 20°C, and heat-set in an electric oven at 120°C for 10 minutes to obtain a polyolefin microporous membrane.
[0109] Example 3 Polyolefin resin A has a weight average molecular weight (Mw) of 2.5×10 5 80% by mass of branched polyethylene with a melting point of 133°C and Mw of 1.0 × 10 6 The same procedure as in Example 2 was repeated, except that a mixture of 20% by mass of homopolypropylene having a melting point of 163°C and 20% by mass of homopolypropylene having a melting point of 163°C was used, and the gel-like sheet was formed by cooling while being taken up at a take-up speed of 6 m / min.
[0110] Example 4 Polyolefin resin A has a weight average molecular weight (Mw) of 2.5×10 5 A mixture of 100% by mass of branched polyethylene having a melting point of 133°C, 29.8% by mass of the polyolefin resin A, and 0.2% by mass of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)-propionate]methane as an antioxidant was fed into a twin-screw extruder, 70% by mass of liquid paraffin was fed from the side feeder of the twin-screw extruder, and the mixture was melt-kneaded under the conditions of a temperature of 160°C, a cylinder rotation speed of 250 rpm, and Q / Ns=0.2 to prepare a polyolefin resin composition A. The polyolefin resin composition A and the polyolefin resin composition B were fed from each twin-screw extruder into a three-layer T-die and extruded into a sheet having a layer structure of A layer / B layer / A layer with a layer ratio of 1 / 5 / 1. The gel-like sheet obtained was cut into a square of 80 mm square, preheated at 110°C for 300 seconds, and simultaneously biaxially stretched at a stretching temperature of 110°C and a stretching speed of 1000 mm / min to 5 times in the MD direction and 5 times in the TD direction. The stretched membrane was washed in a washing tank of methylene chloride to remove liquid paraffin, and the washed membrane was dried in a drying oven adjusted to 20°C, and heat-set in an electric oven at 120°C for 10 minutes to obtain a polyolefin microporous membrane. The same procedure as in Example 2 was carried out except for the above.
[0111] Example 5 Polyolefin resin A has a weight average molecular weight (Mw) of 2.5×10 560% by mass of branched polyethylene with a melting point of 133°C and Mw of 2.5 × 10 6 A mixture of 40% by mass of ultra-high molecular weight polyethylene having a melting point of 127°C, 24.8% by mass of the polyolefin resin A, and 0.2% by mass of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)-propionate]methane as an antioxidant was fed into a twin-screw extruder, 75% by mass of liquid paraffin was fed from the side feeder of the twin-screw extruder, and the mixture was melt-kneaded under the conditions of a temperature of 180°C, a cylinder rotation speed of 250 rpm, and Q / Ns=0.2 to prepare a polyolefin resin composition A. The polyolefin resin composition A was fed into a T-die, extruded into a sheet, and cooled while being taken up at a take-up speed of 4 m / min with a cooling roll adjusted to a temperature of 30°C to form a gel-like sheet.
[0112] The gel-like sheet obtained was cut into a square of 80 mm square, preheated at 110°C for 300 seconds, and simultaneously biaxially stretched 5 times in the MD direction and 5 times in the TD direction at a stretching temperature of 110°C and a stretching speed of 1000 mm / min. The stretched membrane was washed in a washing tank of methylene chloride to remove liquid paraffin, dried in a drying oven adjusted to 20°C, and heat-set in an electric oven at 115°C for 10 minutes to obtain a polyolefin microporous membrane.
[0113] Example 6 Polyolefin resin A has a weight average molecular weight (Mw) of 6.0×10 5 The same procedure as in Example 2 was repeated, except that 80% by mass of high density polyethylene having a melting point of 136°C, 20% by mass of branched polyethylene having a melting point of 125°C and an MFR of 0.4 g / min measured at 190°C and 2.16 kgf, and 29.8% by mass of the above polyolefin resin A and 0.2% by mass of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)propionate]methane as an antioxidant were mixed and fed into a twin-screw extruder, and 70% by mass of liquid paraffin was supplied from the side feeder of the twin-screw extruder.
[0114] Example 7 Polyolefin resin A has a weight average molecular weight (Mw) of 2.5×10 5 60% by mass of branched polyethylene with a melting point of 133°C and Mw of 2.0 × 10 6 The same procedure as in Example 5 was repeated, except that 40 mass % of ultra-high molecular weight polyethylene having a melting point of 133° C. was used.
[0115] Comparative Example 1 Polyolefin resin A has a weight average molecular weight (Mw) of 5×10 4 25% by mass of linear low-density polyethylene having a melting point of 126°C and a weight-average molecular weight (Mw) of 6.0 × 10 5 55% by mass of high-density polyethylene having a melting point of 136°C and a weight-average molecular weight (Mw) of 2.0 × 10 6 20% by mass of ultra-high molecular weight polyethylene having a melting point of 133°C was used, and 24.8% by mass of the polyolefin resin A and 0.2% by mass of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)-propionate]methane, which is an antioxidant, were mixed and fed into a twin-screw extruder, and 75% by mass of liquid paraffin was fed from the side feeder of the twin-screw extruder. The mixture was melt-kneaded under the conditions of a temperature of 160°C, a cylinder rotation speed of 250 rpm, and Q / Ns=0.2 to prepare a polyolefin resin composition A. The polyolefin resin composition A and the polyolefin resin composition B were fed from each twin-screw extruder to a three-layer T-die and extruded into a sheet shape with a layer structure of A layer / B layer / A layer with a lamination ratio of 1 / 1 / 1. The mixture was cooled while being taken up at a take-up speed of 8 m / min with a cooling roll adjusted to a temperature of 30°C. A gel-like sheet was formed. The same procedure as in Example 2 was carried out except for the above.
[0116] Comparative Example 2 Polyolefin resin A has a weight average molecular weight (Mw) of 6.0×10 5 60% by mass of high-density polyethylene with a melting point of 136°C and a weight-average molecular weight (Mw) of 2.0 × 10 6A mixture of 40% by mass of ultra-high molecular weight polyethylene having a melting point of 133°C, 24.8% by mass of the polyolefin resin A, and 0.2% by mass of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)-propionate]methane as an antioxidant was fed into a twin-screw extruder, 75% by mass of liquid paraffin was fed from a side feeder of the twin-screw extruder, and the mixture was melt-kneaded under the conditions of a temperature of 200°C, a cylinder rotation speed of 250 rpm, and Q / Ns=0.2 to prepare a polyolefin resin composition A. The polyolefin resin composition A was fed into a T-die, extruded into a sheet, and cooled while being taken up at a take-up speed of 5 m / min with a cooling roll adjusted to a temperature of 30°C to form a gel-like sheet.
[0117] The gel-like sheet obtained was cut into a square of 80 mm square, preheated at 115°C for 300 seconds, and simultaneously biaxially stretched 5 times in the MD direction and 5 times in the TD direction at a stretching temperature of 115°C and a stretching speed of 1000 mm / min. The stretched membrane was washed in a washing tank of methylene chloride to remove liquid paraffin, dried in a drying oven adjusted to 20°C, and heat-set in an electric oven at 120°C for 10 minutes to obtain a polyolefin microporous membrane.
[0118] Comparative Example 3 The same procedure as in Comparative Example 2 was repeated, except that the film was cooled while being taken up at a take-up speed of 8 m / min using a cooling roll whose temperature was adjusted to 30°C to form a gel-like sheet, and that the film was heat-set in an electric oven at 128°C for 10 minutes.
[0119] [Table 1]
[0120] [Table 2]
[0121] (evaluation) The polyolefin microporous membranes of Examples 1 to 7 have good gloss values, so that the shutdown behavior proceeds uniformly on the film surface and the structural change until shutdown is small, and therefore, when used as a separator for a secondary battery, they can impart excellent shutdown characteristics and high safety, and also have excellent permeability and therefore excellent output characteristics. On the other hand, the polyolefin microporous membranes of Comparative Examples 1 and 2 have low gloss values and high shutdown temperatures, so that when used as a separator for a secondary battery, shutdown takes a long time and the battery stability is insufficient. The polyolefin microporous membrane of Comparative Example 3 has high air permeability and therefore has insufficient output characteristics as a separator for a secondary battery. [Industrial Applicability]
[0122] The polyolefin microporous membrane of the present invention, when incorporated into a secondary battery as a separator, has excellent permeability and can quickly complete shutdown when exposed to high temperatures inside the battery, thereby imparting high safety. Therefore, the polyolefin microporous membrane of the present invention can be suitably used as a separator with excellent safety in secondary batteries, which are particularly required to have high capacity.
[0123] Although the present invention has been described in detail and with reference to specific embodiments, it will be apparent to those skilled in the art that various changes and modifications can be made therein without departing from the spirit and scope of the invention.
[0124] This application is based on a Japanese patent application (Patent Application No. 2019-152107) filed on August 22, 2019, the contents of which are incorporated herein by reference.
Claims
1. The gloss value at an incidence angle of 60° in both the MD and TD directions is 45% or more, and the air permeability converted to a thickness of 10 μm is 250 sec / 100 cm 3 A laminated film as follows, the laminated film comprising a layer A made of a polyolefin resin A containing a polyolefin resin as a main component, and a polyolefin microporous film containing 10 mass% or more of a branched polyethylene relative to the total mass of the layer A.
2. The microporous polyolefin membrane according to claim 1, wherein the laminated membrane is a laminated membrane consisting of at least two layers having different properties.
3. 3. The polyolefin microporous membrane according to claim 1 or 2, wherein the average value of the gloss value in the MD direction and the gloss value in the TD direction at an incident angle of 60° is 50% or more.
4. The microporous polyolefin membrane according to any one of claims 1 to 3, having a shutdown temperature of 135°C or lower.
5. The microporous polyolefin membrane according to any one of claims 1 to 4, having a porosity of 35% or more.
6. The microporous polyolefin membrane according to any one of claims 1 to 5, having an average pore size of 35 nm or less.
7. The microporous polyolefin membrane according to any one of claims 1 to 6, which has a pin puncture strength of 1.5 N or more per 10 µm.
8. The microporous polyolefin membrane according to claim 7, wherein the ratio of the thickness of layer A made of polyolefin resin A to the total thickness of all layers is 50% or less.
9. The polyolefin microporous membrane according to claim 8, which has a plurality of the A layers, and the total thickness of the A layers is 6.0 μm or less.
10. The microporous polyolefin membrane according to any one of claims 1 to 9, having a porous layer comprising inorganic particles and a resin binder on at least one surface thereof.
Citation Information
Patent Citations
Copy prevention method
JP1980036872A
Finely porous membrane of polyethylene
JP2000204188A
Microporous film made of polyethylene and cell obtained using the same
JP2002338730A
Separator for nonaqueous secondary battery, and nonaqueous secondary battery
JP2011129304A
Microporous membrane made of polyethylene and battery using the same
JP2012136704A